Mitigating crop raiding by forest elephants and baboons at Kibale National Park. (19th December 2022) - Kyokuhaire, Anna Muchwampaka; Chapman, Colin A.; Omeja, Patrick A.; Tumusiime, David Mwesigye; Abwoli, Banana Yabezi; Lawes, Michael J.
Abstract: In Africa, most protected forests are in densely human‐dominated landscapes where human–wildlife conflict is intense. We documented farmer perceptions and responses to crop‐raiding wildlife from Kibale National Park, Uganda. Crop raiding was mostly (95%) by baboons ( Papio anubis ) and elephants ( Loxodonta africana ). While the financial loss caused by baboons and elephants did not differ, elephants were perceived as more damaging. Guarding and trenches were perceived as the most effective deterrent strategies for baboons and elephants, respectively. Distance from the park boundary and household income were significantly associated with a greater likelihood of crop raiding. Distance from the park, household head age and the species that raided crops, influenced whether a household applied one or more deterrent strategies. Households headed by women or older adults were most vulnerable, experiencing greater losses to raiding. Patterns of human–wildlife conflict around Kibale forest are complex, but the extent of crop damage was mostly determined by distance from the park and farm socio‐economic status and thus their ability to mitigate or deter raiding. Managing crop raiding requires collaboration between the park and affected farmers to ensure that mutually managed deterrent methods, such as trenching (elephants) and guarding (baboons), are effectively shared, applied and maintained. Résumé: Dans la plupart des pays d'Afrique, les forêts protégées se trouvent dans des paysages à forte densité humaine où les conflits entre l'homme et la faune sauvage sont intenses. Nous nous sommes documentés sur les perceptions et les réactions des agriculteurs face aux animaux sauvages qui pillent les cultures dans le parc national de Kibale, en Ouganda. Les pillages de cultures étaient principalement (à 95%) le fait des babouins (Papio anubis) et des éléphants (Loxodonta africana). Si les pertes financières causées par les babouins et les éléphants ne diffèrent pas, les éléphants sont perçus comme plus dommageables. Le gardiennage et les tranchées ont été perçus comme les stratégies de dissuasion les plus efficaces pour les babouins et les éléphants, respectivement. Les facteurs suivants ont été associés de manière significative à une plus grande probabilité de pillage des cultures : la distance par rapport à la limite du parc et le revenu du ménage. La distance par rapport au parc, l'âge du chef de ménage et les espèces qui attaquent les cultures ont influencé l'application d'une ou plusieurs stratégies de dissuasion par les ménages. Les ménages dirigés par des femmes ou des adultes plus âgés étaient les plus exposés et subissaient des pertes plus importantes en raison des pillages. Les schémas de conflit homme‐faune autour de la forêt de Kibale sont complexes, mais l'étendue des dommages aux cultures a été principalement déterminée par la distance du parc et le statut socio‐économique des fermes et donc leur capacité à atténuer ou à dissuader les pillages. La gestion du pillage des cultures nécessite une collaboration entre le parc et les agriculteurs concernés afin de s'assurer que les méthodes de dissuasion gérées mutuellement, telles que le creusement de tranchées (éléphants) et le gardiennage (babouins), sont effectivement partagées, appliquées et maintenues.